2021
DOI: 10.1016/j.polar.2021.100686
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular polymeric substances in Antarctic environments: A review of their ecological roles and impact on glacier biogeochemical cycles

Abstract: polymeric substances in antarctic environments: A review of their ecological roles and impact on glacier biogeochemical cycles,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 176 publications
(216 reference statements)
0
16
0
Order By: Relevance
“…The activity of EPS to activate macrophages (Zhang et al, 2018) and improve cell viabilities (Yu et al, 2016) supports the role EPS's can play in biomedical fields. Indeed, the role of EPSs from Antarctica isolates on the biogeochemical cycling of calcium and iron in the marine environment, aiding the production and sequestration of dissolved and particulate organic material, aggregation of dust particulates on the surface of the glaciers, and as an essential source of carbon for microorganisms in the food chain have also been recently documented (Bhaskar and Bhosle, 2005;Nagar et al, 2021).…”
Section: Biotechnological Advantages Of Extremophilic Eps Over Traditional Biopolymersmentioning
confidence: 99%
“…The activity of EPS to activate macrophages (Zhang et al, 2018) and improve cell viabilities (Yu et al, 2016) supports the role EPS's can play in biomedical fields. Indeed, the role of EPSs from Antarctica isolates on the biogeochemical cycling of calcium and iron in the marine environment, aiding the production and sequestration of dissolved and particulate organic material, aggregation of dust particulates on the surface of the glaciers, and as an essential source of carbon for microorganisms in the food chain have also been recently documented (Bhaskar and Bhosle, 2005;Nagar et al, 2021).…”
Section: Biotechnological Advantages Of Extremophilic Eps Over Traditional Biopolymersmentioning
confidence: 99%
“…The EPS enables biosorption of trace minerals and sequestration of organic matter and nutrients. 13 , 14 The distinct physical structure of EPS acts as a buffer for microbes in the interior of aggregates to modulate against environmental change and resist adverse environmental effects. 13 , 15 , 16 This buffering and resistance capacity of EPS raises the questions whether the current conjectures of microbial distribution also apply to the methanotrophs and methanogens at soil-water interface, and whether and to what extent the abundance and diversity of these microbes are driven by the environmental factors, such as temperature, soil organic carbon (SOC), soil total nitrogen (STN), metal ions and pH.…”
Section: Introductionmentioning
confidence: 99%
“… 13 , 14 The distinct physical structure of EPS acts as a buffer for microbes in the interior of aggregates to modulate against environmental change and resist adverse environmental effects. 13 , 15 , 16 This buffering and resistance capacity of EPS raises the questions whether the current conjectures of microbial distribution also apply to the methanotrophs and methanogens at soil-water interface, and whether and to what extent the abundance and diversity of these microbes are driven by the environmental factors, such as temperature, soil organic carbon (SOC), soil total nitrogen (STN), metal ions and pH. Furthermore, microbes in PB mostly originate from the underlying soil and constantly exchange and interact with soil microbes, 3 which leads to the question whether there is any association between CH 4 -related microbes in soil and at soil-water interface.…”
Section: Introductionmentioning
confidence: 99%
“…It is reasonable to assume that Antarctic EPSs played a significant role in protecting organisms within ice floes from ice-crystal damage, buffering against pH and salinity fluctuations, and alleviating other chemical stresses such heavy metals though the mechanism was not so evident. It has been found that the molecular weight of EPSs produced by sea-ice isolates is 5-50 times higher than the average of other isolated marine EPSs [10][11][12]. Due to their appealing structure and physicochemical properties, EPSs generated by sea-ice isolates may be useful biosorbents for the removal of heavy metals from saltwater [13].…”
Section: Introductionmentioning
confidence: 99%